(untitled) (Scientific journal of the Fergana State University, 2026)
A study was conducted to study and analyze the distribution, morphology, food spectrum and developmental biology of representatives of the genus Lixus in the Fergana Valley. The studies were conducted in a number of areas of the Vadil, Toshlok, Margilan, Qoshtepa, Bogdod, Buvayda, Beshariq districts of the Fergana Valley. Determining the number of long-nosed beetles and collecting their samples was carried out during the vegetation period of plants starting from March based on the observation method. This article is devoted to the distribution and biology of representatives of the genus Lixus. As a result of the studies, the distribution features, developmental biology and morphological description of representatives of the genus Lixus in the Fergana region were highlighted.